What's so funny? Modelling incongruity in humour production†. Issue 3 (3rd April 2017) - Hull, Rachel; Tosun, Sümeyra; Vaid, Jyotsna
ABSTRACT: Finding something humorous is intrinsically rewarding and may facilitate emotion regulation, but what creates humour has been underexplored. The present experimental study examined humour generated under controlled conditions with varying social, affective, and cognitive factors. Participants listed five ways in which a set of concept pairs (e.g. MONEY and CHOCOLATE) were similar or different in either a funny way (intentional humour elicitation) or a "catchy" way (incidental humour elicitation). Results showed that more funny responses were produced under the incidental condition, and particularly more for affectively charged than neutral concepts, for semantically unrelated than related concepts, and for responses highlighting differences rather than similarities between concepts. Further analyses revealed that funny responses showed a relative divergence in output dominance of the properties typically associated with each concept in the pair (that is, funny responses frequently highlighted a property high in output dominance for one concept but simultaneously low in output dominance for the other concept); by contrast, responses judged not funny did not show this pattern. These findings reinforce the centrality of incongruity resolution as a key cognitive ingredient for some pleasurable emotional elements arising from humour and demonstrate how it may operate within the context of humour generation.